Macrophage potentiates the recovery of liver zonation and metabolic function after acute liver injury - Atsushi Miura (Nature Portfolio, 2021)
Abstract The liver is an exclusive organ with tremendous regenerative capacity. Liver metabolic functions exhibit spatial heterogeneity, reflecting liver zonation. The mechanisms controlling the proliferation of hepatocytes and the accompanying matrix reconstruction during regeneration have been well explored, but the recovery potential of differentiated metabolic functions and zonation after liver injury remains unclear. We employed a mouse model of carbon tetrachloride (CCl4) induced-acute liver injury with clodronate-induced macrophage depletion to clarify the impact of liver injury on liver metabolism and recovery dynamics of metabolic function and liver zonation during regeneration. Depleting macrophages suppressed tissue remodelling and partially delayed cell proliferation during regeneration after liver injury. In addition, recovery of metabolic functions was delayed by suppressing the tissue remodelling caused by the depleted macrophages. The model revealed that drug metabolic function was resilient against the dysfunction caused by liver injury, but glutamine synthesis was not. Metabolomic analysis revealed that liver branched-chain amino acid (BCAA) and carbohydrate metabolism were suppressed by injury. The plasma BCAA concentration reflected recovery of hepatic function during regeneration. Our study reveals one aspect of the regenerative machinery for hepatic metabolism following acute liver injury.